Análise da variação e taxonomia de echinanthera occipitalis (Jan, 1863) (serpentes, colubridae) com a descrição de uma nova espécie - Santos, Alfredo Pedroso dos (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T19:12:23Z (GMT). No. of bitstreams: 1 000382367-Texto+Completo-0.pdf: 1512459 bytes, checksum: 7aa97dd4baa9710ef6d3785f21cfed9c (MD5) Previous issue date: 2005 === The analysis of variation of Echinanthera occipitalis (Jan, 1863) was made on 255 specimens. The species presented variation in the head and neck coloration indicating geographic variation and allowing the description of a new species. After statistical treatment of the external characters and analysis of the hemipeniana morphology, it was evidence that E. occipitalis is composed by groups of species formed by three different taxa, which informally is called occipitalis group. This group is composed by the taxa: E. occipitalis sensu stricto, from northeastern Brazil; E. miolepis (Boettger, 1891), revalidated here; and Echinanthera sp. n., described for the easter Brazilian Amazonia in Para State. === Foi realizada a análise da variação morfológica de Echinanthera occipitalis (Jan, 1863) baseada em 255 exemplares. A espécie apresentou variação na coloração da cabeça e do pescoço indicando variação geográfica e possibilitando a descrição de uma nova espécie. Após tratamento estatístico dos caracteres externos e análise da morfologia hemipeniana, constatou-se que E. occipitalis é formada por um grupo de espécies formado por três táxons, o qual tratamos informalmente como grupo occipitalis. Esse grupo é composto por: E. occipitalis sensu stricto, própria da região Nordeste do Brasil; E. miolepis (Boettger, 1891), revalidada neste trabalho; e Echinanthera sp. n., ocorrente no leste da Amazônia brasileira, Estado do Pará.